Technological reliability of chemical engineering systems - N. N. Prokhorenko; K. O. Goncharuk (Тонкие химические технологии, 2016)
A significant part of the gross domestic product is lost because of hitches followed by long downtime periods in industrial systems. This is a common problem in the industry of developed nations. Analysis of causes of this phenomenon allows developing a conception of solving this problem and suggesting a method of studying the reliability (working capacity) of chemical-engineering systems (CES). In this article we prove the need for technological reliability analysis tools in prefeasibility study to estimate the potential working capacity of the technology and to avoid the large costs of starts and stops.